1985
DOI: 10.1007/bf01870777
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the electromotive force of active sodium transport in frog skin epithelium (Rana temporaria) from presteady-state flux ratio experiments

Abstract: The presteady-state influxes and effluxes of sodium across frog skin epithelium have been determined as a function of time while all electrophysiological parameters were maintained constant. The fluxes measured were resolved in the fractions which have passed a pathway through the cells and those that have used a paracellular pathway. The procedure is based on the theory that all presteady-state flux ratios have to be equal to the steady-state flux ratio if only one pathway is involved. The flux ratios for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The Ca-fluxes are equal. The sum of the passive ion flows for Nae and Ca-(partial ionic conductances) was -80% ofthe measured G. The disparity between the partial ionic conductances and G may represent the contribution of unmeasured solution ions (e.g., HCO3), the conductances associated with the active Na' path (apical GN.+, basolateral GK [17,18]), or both. Although there is a trend for Isc to be slightly increased in atopic polyp epithelia, no systematic differences 15 between any baseline parameters ofatopic polyp (n = 8 subjects)…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The Ca-fluxes are equal. The sum of the passive ion flows for Nae and Ca-(partial ionic conductances) was -80% ofthe measured G. The disparity between the partial ionic conductances and G may represent the contribution of unmeasured solution ions (e.g., HCO3), the conductances associated with the active Na' path (apical GN.+, basolateral GK [17,18]), or both. Although there is a trend for Isc to be slightly increased in atopic polyp epithelia, no systematic differences 15 between any baseline parameters ofatopic polyp (n = 8 subjects)…”
Section: Resultsmentioning
confidence: 94%
“…We do not know the permeability of the paracellular path to mannitol in situ. However, the relatively high Pm.,,it., values (30-40 X lo-cm -s-') measured in nasal epithelia as compared with excised canine or human bronchi (15)(16)(17)(18)(19)(20) X lo-cm s-') (9,24), raise the possibility that physical damage may have occurred to the specimens during the operative excision and/or mounting procedure. Such damage would create nonselective leaks in the epithelial barrier that would serve to partially shunt the transepithelial PD.…”
Section: Discussionmentioning
confidence: 99%
“…The reversal potential of pump currents is E pump rev ¼ ÀE pump with free energy of ATP hydrolysis, ΔG ATP % À60 kJ/mol and stoichiometry of 3 Na + :2 K + :1 ATP, E pump is about 200 mV which is within the range discussed by de Weer et al (1988) and used in all our computations independently of the rate of pump flux. Unlike the reversal potential of the Na + pump of a tight epithelium, e.g., frog skin (Larsen 1973;Eskesen and Ussing 1985), the last mentioned assumption is plausible for proximal tubule cells of high density of mitochondria in remarkably close contact with pump sites that would minimize the diffusion distance between sites of dephosphorylation of ATP and rephosphorylation of ADP, respectively (Dørup and Maunsbach 1997). Following Läuger (1991), by inspection of Eq.…”
Section: àmentioning
confidence: 99%
“…In an experimental study designed by Ussing of the mechanism of isosmotic transport by the small intestine, Nedergaard et al (1999) observed that sodium ions are recirculated from the serosal solution via cells back into the lateral intercellular space, which suggested a mechanism for regulating the osmolarity of the transported fluid. In the small intestine (Larsen et al 2002) and amphibian skin (Larsen et al 2009), the recirculation pathway would be the 1Na:2Cl:1K cotransporter studied by Frizzell et al (1979), Ferreira (1981), andUssing (1985), respectively. In the heterocellular proximal tubule with absorption of Na + , Cl À , and HCO 3 À , one would expect that different segments handle recirculation by different cotransporters depending on whether Cl À or HCO 3 À are transported together with Na + .…”
Section: Isosmotic Transportmentioning
confidence: 99%